EVALUATION OF CARBAPENEM USE AMONG PATIENTS AT INTENSIVE CARE UNIT (ICU) IN SANA'A, YEMEN - Alyahawi, Ali; Alrubaiee, Gamil; Alkaf, Ali (Universal Journal of Pharmaceutical Research, 2020)
Objective: Drug Utilization Evaluation (DUE) studies are designed to evaluate and improve the rational use of medications. In this study, DUE has focused on drugs used in high risk patients such as critically ill cases. Carbapenems are beta-lactam type antibiotics with broad-spectrum of activity which cover gram-positive, gram-negative and anaerobic bacteria. The heavy use of carbapenems (imipenem or meropenm) could increase the risk of multi-drug resistant (MDR) pathogens. This study was a prospective and cross sectional study performed at intensive care unit (ICU) of Al-Matwakel hospital in Sana'a, Yemen. Methods: The study was conducted from September 2018 to March 2019. All of the patients were on imipenem or meropenem as an empiric treatment or based upon microbiology culture results included in the study. Total of 80 patients at ICU were evaluated. Results: The results of the study showed that empiric therapy was in most cases (91.25%; P<0.001).In addition; about 36.3% of the patients required dosage adjustment according to glomerular filtration rate (GFR) stages. Also according to GFR calculation, 43.8% of the patients were in stage 3. In the present study, the frequency of therapeutic duplication of ceftriaxone with carbapenem was reported in 38 patients. The major drug-drug interactions were observed with tramadol-imipenem, tramadol-meropenem, and amlodipine-simvastatin. Conclusion: The result of the study showed that empiric therapy was unjustified in most cases (91.25%). In addition, about 36.3% of the patients required dosage adjustment according to GFR stages. According to GFR calculation, 43.8% of the patients were in stage 3. In the present study, the frequency of therapeutic duplication and drug-drug interactions were observed. Peer Review History: Received 8 October 2019; Revised 11 November; Accepted 27 December; Available online 15 January 2020 Academic Editor: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Reviewer(s) detail: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Dr. Mahmoud S. Abdallah , University of Sadat city, Egypt, dr_samy777@yahoo.com